Effectiveness of SK Mandatory Training Conducted in Selected Barangays of Cebu City - Cal, Ma. Sonia Fate C.; Abellanosa, Melissa C.; Payao, Ronald B.; Niere, Marvin Ian E. (Future Science / FSH-PH Publications, 2023)
All SK Officials are mandated by the SK Reform Act and ordered by the Department of Interior and Local Government to undergo the SK Mandatory Training. This study is intended to assess the effectiveness of the SK Mandatory Training as conducted in selected barangays of Cebu City. It aims to check the extent of the variables. The method utilized in this study was the descriptive correlational design. Survey Questions were drawn from the five training modules, viz.: Decentralization and Local Governance, SK History, Meetings and Resolutions, Planning and Budgeting, Code of Conduct, and Ethical Standards. There were 160 respondents; 124 SK Councilors and 36 SK Chairpersons from different barangays of Cebu City. Based on Pearson product-moment correlation, it was revealed that there is a strong, positive correlation between knowledge and demonstration. It was also shown by the results that; SK Officials were very knowledgeable with a grand mean of 3.58 and have highly demonstrated a grand mean of 3.57. Therefore, the researchers concluded that the SK Mandatory Training conducted for the SK Officials of Cebu City was effective.